Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1097/sla.0b013e31820b8d52
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative High-resolution Magnetic Resonance Imaging Can Identify Good Prognosis Stage I, II, and III Rectal Cancer Best Managed by Surgery Alone

Abstract: The preoperative identification of good prognosis tumors using MRI will allow stratification of patients and better targeting of preoperative therapy. This study confirms the ability of MRI to select patients who are likely to have a good outcome with primary surgery alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
329
1
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 553 publications
(365 citation statements)
references
References 0 publications
13
329
1
14
Order By: Relevance
“…Bei in der Dünnschicht-MRT bestimmter radialer Tumorinfiltration unter 5 mm (cT3a/b) und ausreichendem Abstand zur mesorektalen Faszie ist bei adäquater TME ein dem Stadium I vergleichbares Lokalrezidivrisiko anzunehmen [981], sodass in dieser Konstellation auf eine neoadjuvante Radio(chemo)therapie verzichtet werden kann, wenn keine zusätzlichen Risikofaktoren (z. B. tiefliegender Tumor, eindeutiger Lymphknotenbefall, EMVI) vorliegen und eine nachvollziehbar hohe Qualität der MRT sowie der TME-Chirurgie am Zentrum gegeben ist [982]. …”
Section: Starker Konsensunclassified
“…Bei in der Dünnschicht-MRT bestimmter radialer Tumorinfiltration unter 5 mm (cT3a/b) und ausreichendem Abstand zur mesorektalen Faszie ist bei adäquater TME ein dem Stadium I vergleichbares Lokalrezidivrisiko anzunehmen [981], sodass in dieser Konstellation auf eine neoadjuvante Radio(chemo)therapie verzichtet werden kann, wenn keine zusätzlichen Risikofaktoren (z. B. tiefliegender Tumor, eindeutiger Lymphknotenbefall, EMVI) vorliegen und eine nachvollziehbar hohe Qualität der MRT sowie der TME-Chirurgie am Zentrum gegeben ist [982]. …”
Section: Starker Konsensunclassified
“…For MRI-based treatment he calculated a 5% increase of the absolute risk of LR for "best case", i.e., specialized centers and 12% in "worst case", i.e., institutions with lower quality of MRI and less expertise in terms of achieving an optimal plane of surgery. The attempt to use MRI to optimize preoperative diagnostic work-up was extensively investigated by the MERCURY study group who demonstrated the diagnostic accuracy of MRI in patients who were either primarily operated or underwent nRCT according to the predicted CRM [29,43]. They provided the first publication of 5-year data correlating mr-CRM and LRR with surgery alone.…”
Section: Can Mri Predict Prognosis?mentioning
confidence: 99%
“…A negative CRM (defined as ≥1 mm on pathological work-up) has consecutively been identified and validated as an important surrogate parameter to predict the individual LR risk [12]. Results of the MERCURY study group (Magnetic Resonance Imaging in Rectal Cancer European Equivalence Study) whose authors propagated and investigated MRI-based treatment for rectal cancer were encouraging [23,43] and promoted similar attempts in the German-speaking community such as the OCUM study (optimized surgery and MRI-based multimodal therapy of rectal cancer). Preliminary results were recently published [22,42] and are commented in this editorial.…”
mentioning
confidence: 99%
“…Presently standardised techniques in magnetic resonance imaging (MRI) of the rectum have allowed a radiological defi nition of rectal cancer whereby the possibility of surgery completely removing the disease can be shown preoperatively [1,2]. From this a categorisation of risk based on MRI and clinical staging can be developed as follows:…”
Section: Or Why Translational Research Is Vital For the Future Treatmmentioning
confidence: 99%